IMPLEMENTING CHARACTER EDUCATION AS SOLUTION OF CHILDREN MORAL DECADENCE - Luqman Nurhisam (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
Character education is an important issue in the world of late-adult education. This is related to the phenomenon of moral decadence that occurs in the midst of society as well as in an increasingly diverse government environment. Among others include crime, injustice, corruption, violence in children, to the violation of human rights. This proves that there is indeed a crisis of identity and characteristics of the Indonesian nation. The existence of character education becomes an appropriate answer to the various problems that have been mentioned previously. It is known that character education is defined as education which develops character values in children so that they have values and character as their character, apply those values in their life, as members of society and religious, nationalist, productive and creative citizens. School as a place of education providers is expected to be a place capable of realizing the mission of character education.